2022
DOI: 10.3389/fpsyg.2022.1024139
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between organizational commitment and turnover intention among temporary employees in the local government: Mediating role of perceived insider status and moderating role of gender

Abstract: PurposeThe purpose of this study is to examine the relationships between organizational commitment and turnover intention, and to test the mediating effect of perceived insider status, and moderating effect of gender on that relationship.MethodologyData were collected using a questionnaire survey method from 820 temporary employees of government agencies working in China. The data obtained were analyzed according to the moderated mediation.FindingsAs a result of the analysis, it was determined that perceived i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…This is based on the results of the calculation of the original sample value of -0.419 and the t-statistic value of 5.191 ≥ 1.96 so that H3 is accepted. This research is in line with Dwilingga (2017), Ayari & AlHamaqi (2022), Xia et al (2022), andZhu et al (2022) which reveal that organizational commitment has a negative and significant effect on turnover intention.…”
Section: Organizational Commitment On Turnover Intentionsupporting
confidence: 88%
“…This is based on the results of the calculation of the original sample value of -0.419 and the t-statistic value of 5.191 ≥ 1.96 so that H3 is accepted. This research is in line with Dwilingga (2017), Ayari & AlHamaqi (2022), Xia et al (2022), andZhu et al (2022) which reveal that organizational commitment has a negative and significant effect on turnover intention.…”
Section: Organizational Commitment On Turnover Intentionsupporting
confidence: 88%
“…Organizational commitment has also been found to considerably influence performance and moderate the association between total job stress and performance. Previous research has shown that workers' perceptions of their organizations' support are favorably associated with their organizational commitment and adversely related to their desire to leave their current positions and turnover intention [63][64][65]. Thus, H6 explains the observed relationship between OC and TI.…”
Section: Discussionmentioning
confidence: 88%
“…This study demonstrated that in government agencies, insider status somewhat moderated the connection between loyalty to the company and a desire to leave. For both sexes, perceived insider status had a reduced indirect influence on organizational commitment and turnover intention [65]. Employees' intentions to leave the company were shown to be significantly inversely related to their level of commitment to PT.…”
Section: Relationship Between Oc and Timentioning
confidence: 89%
“…For Chung et al (2017), job stress affects employees' desire to leave the organization, and a lack of commitment will reduce employees' efforts to work and lead to the emergence of the propensity to leave (Boroş and Curşeu, 2013). This is aligned with Dwiyanti and Kusuma Abdilla (2018) that low job insecurity will increase organizational commitment among nontenured employees, which is further supported by Xia et al (2022) that organizational commitment of temporary government employees is negatively correlated with turnover intention. With all these pre-existing studies, we can assume that the security of the job is related to employees' commitment to an organization, but what facilitates or hampers their organizational commitment still needs to be explored, and that forms part of the questions of this research.…”
Section: Introductionmentioning
confidence: 85%